Pengaruh Sistem Informasi E-Ticketing Terhadap Loyalitas Konsumen di PT. Cahaya Bersama - Hasjim, Alifya Farahusna Putrie; Hanifa, Nurul (Jurnal Ekonomika : INDEPENDEN, 2023)
This study aim to know the effect of e-ticketing information system on customer loyalty in PT. Cahaya Bersama. This study uses a quantitive research methods with descriptive analysis explanatory approach. Sampling uing random sampling technique. The analysis technique used in this study is simple linier regression. The resukts ofthis study indicate that the variable e-ticketing information system significantly affect consumer loyalty in PT. Cahaya Bersama along with obtaining the calculated t value 19.41031 > t table 1.984217.